Success of Endoscopic Surgery in Nasal Polyposis - Waqas Javaid, Hira Andleeb, Abid Rashid, Raana Amir Akbar, Syed Tauseef Bukhari, Tarique Khan, Syed Qasim Ali Jafri, Maryam Fatima, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Endoscopic Sinus Surgery is a minimally invasive procedure that involves the use of an endoscope to improve sinus airflow and drainage as well as the removal of polyps. The extent of surgery varies depending on the severity of the condition and the surgeon's experience. This method has been utilized to treat sinonasal problems for over a decade. Aim: To find the frequency of success of Endoscopic Surgery in patients of Nasal Polyposis. Study design: Descriptive (Prospective) case series. Setting & duration: Department of ENT Unit II, Sir Ganga Ram Hospital, Lahore from 27-01-2021 to 26-07-2021. Methods: In current study, 80 patients of Nasal Polyposis were enrolled. All Patients were undergone Endoscopic Surgery procedure, following the patient at 3 weeks post-operatively as per operational definition addressed by success. Post-stratification chi-square test was applied. Results: Regarding age distribution, mean age was observed 37.60±4.479 years ranged from 30 to 45 years.35 patients were below 38 years of age whereas 45 patients were either 38 years or above. Out of 80 patients, 44 patients (55%) were male while remaining 36 patients (45%) were female. Frequency of patient success after Endoscopic surgery in Nasal polyposis was 64(80%). Conclusion: In conclusion, the success of the patients was considered to be high and comparable to recent literatures both local and international. The percentage of success of patients was higher i.e. 80%.